A study of risk factors and clinical characteristics of neonatal pneumonia in a tertiary care centre - Syeda, Arshiya; Reddy, Lohith; Ksl Sowmya; Manta, Santosha; Ahmed, Nisar (International Journal of Contemporary Pediatrics, 2023)
Background: Neonatal pneumonia accounts for significant morbidity and mortality, especially in developing countries. Throughout childhood, the greatest risk of death from pneumonia is in the neonatal period. This study is done to study the risk factors and clinical characteristics of neonatal pneumonia. Aim of the study was to study the risk factors and clinical characteristics of neonatal pneumonia. Methods: This was a hospital-based observational study conducted in the department of paediatrics, Gandhi medical college and hospital, Hyderabad. A detailed antenatal and postnatal risk factors were taken, and the clinical signs and symptoms of neonatal pneumonia were noted. Results: Of the 100 neonates 30% of cases had early onset pneumonia and 70% had late onset pneumonia.50% of early onset pneumonia cases had antenatal risk factors. There is a statistically significant association of age of onset of pneumonia with gestational age (p=0.002) late onset pneumonia being more common >37 weeks of gestational age. 80% of early onset pneumonia cases were associated with septicaemia. Conclusions: Pneumonia is one of the most common causes of respiratory distress in neonates. Late onset pneumonia was more common. Major predisposing factors for early onset pneumonia are antenatal risk factors like premature rupture of membranes, maternal fever, major predisposing factors for late onset pneumonia are pre-lacteals, oil instillation in the nose, and aspiration of milk. Cough as a symptom was observed in late onset pneumonia.